2020
DOI: 10.3390/md18020114
|View full text |Cite
|
Sign up to set email alerts
|

The Biological and Chemical Diversity of Tetramic Acid Compounds from Marine-Derived Microorganisms

Abstract: Tetramic acid (pyrrolidine-2,4-dione) compounds, isolated from a variety of marine and terrestrial organisms, have attracted considerable attention for their diverse, challenging structural complexity and promising bioactivities. In the past decade, marine-derived microorganisms have become great repositories of novel tetramic acids. Here, we discuss the biological activities of 277 tetramic acids of eight classifications (simple 3-acyl tetramic acids, 3-oligoenoyltetramic acids, 3-decalinoyltetramic acid, 3-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 207 publications
(383 reference statements)
0
41
0
Order By: Relevance
“…Nevertheless, the earnest efforts contributed all over the world by researchers with a focus on MNPs discovery have been able to evolve a few potential antiparasitic compounds from more than a few marine organisms, namely the cyanobacterial linear lipodepsipeptide, symplostatin 4 (Sym4)/gallinamide A containing a methylmethoxypyrrolinone (MMP) moiety from Schizothrix sp., and carmaphycin (two leucine-derived a,b-epoxyketone containing modified peptides) from another marine cyanobacterium Symploc a sp. [ 20 ] (studied extensively) [ 21 ]. Other isolated marine natural products need to follow suit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the earnest efforts contributed all over the world by researchers with a focus on MNPs discovery have been able to evolve a few potential antiparasitic compounds from more than a few marine organisms, namely the cyanobacterial linear lipodepsipeptide, symplostatin 4 (Sym4)/gallinamide A containing a methylmethoxypyrrolinone (MMP) moiety from Schizothrix sp., and carmaphycin (two leucine-derived a,b-epoxyketone containing modified peptides) from another marine cyanobacterium Symploc a sp. [ 20 ] (studied extensively) [ 21 ]. Other isolated marine natural products need to follow suit.…”
Section: Resultsmentioning
confidence: 99%
“…Qin et al in a study which showed that soft corals are rich in natural products exploited Sinularia sp., and isolated 21 terpenoids: sinuketal (1), sinulins A and B (2 and 3) (sesquiterpenoids), sinulins C and D (4 and 5) (cembranoids) (Fig. 3i), known sesquiterpenoids (6-13) and cembranoids (14)(15)(16)(17)(18)(19)(20)(21). Unexpectedly, the first marine-derived compound having isopropyl-type bicyclo [6.3.0] undecane carbon skeleton with unique endoperoxide moiety is sinuketal (1).…”
Section: μMol/l)mentioning
confidence: 99%
“…Their polycyclic system is categorized into three main groups: the PTMs containing a 5/5, those with a 5/6/5, or PTMs with a 5/5/6 ring system in their structure (Luo et al, 2013;Liu et al, 2019). PTMs are well-known for possessing various biological activities such as antibacterial, antifungal, antiprotozoal, and antiviral (Luo et al, 2013;Liu et al, 2019;Jiang et al, 2020). For example, capsimycin B was discovered from Streptomyces sp.…”
Section: Production Of Bioactive Ptms and The Siderophore Mirubactin mentioning
confidence: 99%
“…Secondly, it is plausible that production and secretion of the bioactive PTMs (2-7) by endophytic S. pulveraceus ES16 can provide a competitive advantage to the bacterium in the host plant apoplast because it can ward off a plethora of pathogens or associated endophytes, thereby enabling better colonization and increased abundance of the endophyte in the host. However, some of the endophytic PTMs possess cytotoxic activities in addition to having antimicrobial efficacies (Luo et al, 2013;Liu et al, 2019;Jiang et al, 2020). Whether these compounds also negatively affect the host plant by exerting phytotoxic effects should be studied in the future.…”
Section: Insights Gained From the Chemical Evaluation Of Endophytic Smentioning
confidence: 99%
“…Marine-derived fungi are a significant source of pharmacological molecules with interesting and diversified structural properties [1][2][3][4]. Among them, the fungal genus Alternaria had a widespread distribution in marine source [4] (including sediment [5], sponge [6], alga [7], mangrove [8], soft coral [9]) and could produce plenty of structural molecules, including nitrogen-containing compounds, steroids, terpenoids, pyranones, quinones, and phenolics [10]. These metabolites exhibited a variety of biological activities such as cytotoxic, antimicrobial, enzyme inhibitor properties [10].…”
Section: Introductionmentioning
confidence: 99%